GERD for the nongastroenterologist: successful evaluation, management, and lifestyle‐based symptom control. Issue 1 (17th September 2020) - Stein, Ellen; Sloan, Josh; Sonu, Irene; Kathpalia, Priya; Jodorkovsky, Daniela
Abstract: Gastroesophageal reflux disease (GERD) is a complex disorder. Symptoms of heartburn can help find the disorder of GERD. pH testing is the mainstay of evaluation of symptoms, including 24‐h and longer pH studies to detect pathologic acid exposure. The use of proton pump inhibitor (PPI) therapy for approved indications is helpful for both symptomatic relief and esophagitis healing in the majority of patients with abnormal acid exposure. PPI medications are safe in short‐ or long‐term use. It is recommended not to maintain cirrhotic patients on PPI therapy without a meaningful indication. Dietary adjustment can provide benefit to some patients, but the data are mixed on how much benefit has been demonstrated from specific food avoidance. Reduction in weight improves reflux. Obesity has measurable effects on the esophageal acid exposure but fewer effects on the motility of the esophagus itself. Controlling weight and changing lifestyle can be helpful for improving GERD symptoms. For some patients in whom either the control of reflux with medications and lifestyle change is not sufficient or a hernia is contributing to symptom generation, surgical and endosurgical interventions can be considered to help manage reflux after a thorough workup with pH testing and manometry. Abstract : In clinical practice, testing can be used to identify pathologic reflux, including endoscopic findings, pH testing results, and esophageal manometry. Certain findings have a greater correlation with GERD, while others are more loosely associated, because it is a complex disorder. For some patients in whom the control of GERD with medications and lifestyle change is not sufficient or in whom a hernia is contributing to symptom generation, surgical and endosurgical interventions can be considered to help manage reflux after a thorough workup with pH testing and manometry.